2020
DOI: 10.3390/ijerph17238839
|View full text |Cite
|
Sign up to set email alerts
|

Reopening Schools during the COVID-19 Pandemic: Overview and Rapid Systematic Review of Guidelines and Recommendations on Preventive Measures and the Management of Cases

Abstract: Given the limited evidence of school closure effectiveness in containing the pandemic and the consequences for young people, reopening schools with appropriate measures is essential. This overview aimed to describe the main measures planned for the 2020–2021 academic year within the WHO European Region. A rapid systematic review of scientific databases was also performed. The websites of the government, Ministry of Health, and Ministry of Education of European Region countries were searched through 1 October f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 26 publications
2
44
0
6
Order By: Relevance
“…From May 22, children were able to go outside without time limitations. In September 2020, face-to-face educational activity was resumed, adopting a series of prevention, hygiene, and health promotion measures against COVID-19 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…From May 22, children were able to go outside without time limitations. In September 2020, face-to-face educational activity was resumed, adopting a series of prevention, hygiene, and health promotion measures against COVID-19 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings hold a potential implication to inform both the governance decisions and specific measures taken in updated school re-opening procedures for future emergencies, natural disasters, and infectious disease outbreaks. Indeed, a recent literature review conducted in the European Region of the World Health Organization reported both a lack of government documents and data on policy consensus for schools among high-risk vulnerable sub-populations, as well as for after positive test results [ 44 ]. Future research should focus on both the physical S&H of students and HS educational professionals, as well as their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…El cierre de escuelas fue considerado generalmente como el último recurso para el control de la COVID-19. Las recomendaciones sobre el cierre escolar coincidían en su mayoría en que esta medida debía ser el último recurso para el control de la pandemia, no así en los criterios para el regreso a la escuela de los estudiantes que dieron positivo y la flexibilidad entre la asistencia a la escuela y la educación remota para los niños de alto riesgo 35 . La Organización Panamericana de la Salud (OPS) publicó una guía que analizó las consecuencias sanitarias, sociales y económicas de las medidas tomadas para el control de la pandemia relacionadas con el cierre de escuelas, así como los elementos que deben tenerse en cuenta a la hora de reabrirlas, con un enfoque en la niñez y la adolescencia en situaciones de vulnerabilidad.…”
Section: Cierre Vs Apertura Escolar ¿Cuándo Cómo Y Durante Cuánto Tiempo?unclassified